Waste-to-fuel: The potentials of waste hard nutshell oil and biowaste heterogeneous catalysts for biodiesel production - Abiodun Oladipo; Onome Ejeromedoghene; Oluwafemi Kehinde Olaseinde; Victor Enwemiwe; Kingsley Azubuike Samson (Next Sustainability)
Many developing countries face severe environmental challenges due to improper waste disposal and reliance on fossil fuels for energy production. The global dependence on fossil fuels has exacerbated environmental degradation, highlighting the urgent need for sustainable alternatives with reduced greenhouse gas emissions. Biofuels, particularly biodiesel, offer significant environmental advantages over diesel, including lower emissions and improved engine performance. This review explores the potential of waste hard nutshell oil as a sustainable biodiesel feedstock and evaluates the suitability of biowaste materials as heterogeneous catalysts. Key methods include advanced extraction techniques for hard nutshell oil, theoretical simulations to optimize production processes, and circular economy principles to minimize waste and maximize resource efficiency. The findings demonstrate that waste-to-fuel strategies, utilizing hard nutshell oil and biowaste catalysts, provide a viable and eco-friendly alternative to fossil fuels. Theoretical simulations enhance production efficiency, while circular economy approaches ensure sustainability. This review highlights the transformative potential of waste hard nutshell oil and biowaste catalysts in biodiesel production, offering a sustainable solution to reduce fossil fuel dependency, address environmental challenges, and advance clean energy development.